STUDENTS’ PERCEPTION ON THE USE OF GOOGLE CLASSROOM AS LEARNING MEDIUM AT SMA NEGERI 1 BANTAENG - Hisaan, Amalia Khoirotun; Salija, Kisman; Korompot, Chairil Anwar (Universitas Negeri Makassar, 2023)
The objective of this research is to find out how do the students perceive on the use of Google Classroom as learning medium at SMA Negeri 1 Bantaeng. This research used a descriptive qualitative approach. Students in the XII grade made up the study's population. at SMA Negeri 1 Bantaeng for the 2022/2023 academic year. A simple random sampling technique was utilized in this study. The sample was class XII MIPA 1, which consisted of 34 students, a total of 14 students from class XII MIPA 1 became informants in this research. The instrument used in this research was interview. The result of this research indicated that the three aspects based on Davis’s theory perceive of usefulness, perceive of ease of use, and students’ satisfaction received positive responses. It means that the students’ perceived Google Classroom is the students are satisfied, useful and also easy to use technology as learning medium.